Variasi Makna Lafaz Al-Umm dalam Al-Qur’an - Syukran Abu Bakar; Husna Khairudita (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2021)
This paper discusses the pronunciation of al-Umm contained in the Qur'an. In general, the word al-Ummmeans a mother who gives birth. The pronunciation of al-Umm in the Qur'an does not only mean mother, and it can vary in meaning when based on other sentences. Departing from the variations in pronunciation base, the author needs to investigate the use of pronunciation of al-Umm in the Qur'an deeply. This is library research. The data were collected using the Mawḍu'i method (thematic method) and the al-Wujuh wa al-Nazhair approach. The author's sources of data are al-Mu'jam (language dictionary), books of Ulum al-Qur'an, and books of interpretation (Tafsir). The results of the study presented that the pronunciation of al-Ummis mentioned in the Qur'an in the form of singular, plural and word sequences. The 28 words indicate a mother's figure's meaning from 35 words, while the other 7 have their meanings when juxtaposed with other words. The pronunciation of al-Umm is not related to the time or place where the Qur'an was revealed, both in Mecca and Medina. The pronunciation of al-Umm besides means a mother who is pregnant, gives birth, breastfeeds, and the wives of the Prophet, it also means Umm al-Qura (Mecca), Umm al-Kitab (Lauhul-Mahfuzh), and the place of return. Tulisan ini membahas tentang lafaz al-umm yang terdapat di dalam Alquran, umumnya lafaz al-umm bermakna ibu yang melahirkan, ternyata di dalam Alquran, lafal al-umm tidak hanya bermakna ibu, lafaz al-umm bisa bervariasi maknanya jika disandarkan kepada kalimat lain, berangkat dari adanya variasi penyandaran lafaz tersebut, penulis perlu meneliti lebih dalam terkait penggunaan lafaz al-umm di dalam Alquran. Penelitian ini bersifat kepustakaan (library research), data ditelusuri melalui metode mawḍu’i (metode tematik), dengan menggunakan pendekatan ilmu al-Wujuh wa al-Nazhair. Sumber data yang penulis rujuk adalah kitab al-mu’jam(kamus bahasa), kitab-kitab ulum Alquran, kitab-kitab tafsir,. Hasil dari penelitian ini menunjukkan bahwa lafaz al-Umm disebutkan dalam Alquran berupa lafaz tunggal, jamak dan rangkaian kata, 28 kata menunjukkan makna sosok seorang ibu dari 35 lafaz, sedangkan 7 lainnya memiliki makna tersendiri ketika disandingkan dengan kata lain, lafaz al-Umm ini tidak ada sangkut pautnya dengan waktu atau tempat diturunkannya Alquran, baik Makkiyyah maupun Madaniyyah. Adapun makna dari lafaz al-Umm selain berupa makna ibu yang mengandung, melahirkan dan menyusui, istri-istri Nabi, juga bermakna Umm al-Qura (Mekkah), Umm al-Kitab (Lauh al-Mahfuz), dan tempat kembali.